Iowa Birdline update, March 1, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email for the Iowa Birdline update for March 1, 1993. Highlights of the update include sightings of the continued presence of two Townsend's Solitaires, a Great Black-backed Gull and three Short-eared Owls. Also included are handwritten notes for the next week's update with sightings of a Common Redpoll and a male Greater Scaup. Epson - sheet feed/flatbed